Between Policy and Practice: Unveiling School Leaders' Unawareness of Volunteer Teacher Guidelines - Patrick Manyengo (Managere: Indonesian Journal of Educational Management, 2025)
This study examines the implementation gap between national policies and volunteer teacher management practices in public secondary schools. Using a qualitative case study approach with semi-structured interviews with 18 principals as well as an analysis of the 2023 national policy document, the study identified three key findings: first, the majority of school principals were unaware of the existence of the 2023 Volunteer Teacher Guidelines, so recruitment was carried out without standard procedures and formal employment contracts. Second, informal recruitment practices, such as through parent meetings or referrals from TAESA, are adaptive strategies but weaken the principles of transparency and accountability. Third, the incentive and recognition system for volunteer teachers is sporadic and unstructured, which strengthens the marginal position of volunteer teachers in the education system. This gap reflects the weak dissemination of policies, the lack of training for school principals, and the limitations of institutional capacity in the context of education decentralization. This study recommends strengthening policy socialization, providing continuous training, implementing regulation-based incentives, and integrating volunteer teachers into national training programs to achieve an inclusive, equitable, and sustainable education system.